Generic Paradoxical Tensions, Appraisals, Work Motivation, and Performance: Insights From a Weekly Repeated-Measures Study - Tripathi, Neha (Frontiers in Psychology, 2021)
Drawing on paradox theory, I develop a theoretical model of appraisal-motivational responses to generic paradoxical tensions. I postulate that paradoxical tensions are appraised both as challenge and as threat, in turn prompting mixed effects—positive and negative—on performance. The dual effects of paradoxical tensions are explained by intermittent role of motivation towards the work and a dispositional boundary condition—individual’ adaptability—cross-situation variability of behaviors. The results from a weekly repeated measures study conducted for eight consecutive weeks spanning a period of two months (N=178, total observations = 1,355) provided support for the proposed theoretical model. By illuminating nuanced intraindividual psychological process, the present study brings forward novel insights on cognitive appraisals and motivations of paradoxical tensions advancing microfoundation of the paradox research.